Therapeutic Applications of Nanozymes in Chronic Inflammatory Diseases. (11th August 2021) - Wang, Haojue; Cui, Zichen; Wang, Xuan; Sun, Shui; Zhang, Dongsheng; Fu, Chuanyun
Abstract : Since the discovery of horseradish peroxidase-like activity of magnetite nanoparticles in 2007, many researchers have investigated different types of nanoparticles that show enzyme-like activities, namely, nanozymes. Nanozymes possess high efficiency, stability, and low production costs compared to natural enzymes. Thus, nanozymes have already been widely studied in various domains including medical science, food industry, chemical engineering, and agriculture. This review presents the utilization of nanozymes in medicine and focuses particularly on their therapeutic applications in chronic inflammatory diseases because of their antioxidant-like activity. Furthermore, the treatment of chronic inflammatory diseases with nanozymes of different materials was introduced emphatically.